The Effect Of Problem-Solving Learning Methods On The Accuracy Of Underhand Passes In Girls' Volleyball At SMP N 2 Hamparan Perak Deli Serdang - Jualina Widyawaty; Jenas Pardomuan Sihotang; Jepni Piola Togatorop; Iwan Julius Gulo; Jhon Ferinando Tarigan (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
The influence of problem-solving learning methods on the accuracy of underhand passing in women's volleyball is the driving force of this research. SMPN 1 Pulau Merbau, Teluk Ketapang Village, Pulau Merbau District. Students have not shown their greatest potential in Underhand Passing, therefore errors often occur in that part of the test. This research is a Quasi-Experimental research, with the title